Pengaruh Soft Skill, Hard Skill, dan Pengalaman Organisasi terhadap Kesiapan Kerja Mahasiswa Institut Bisnis dan Teknologi Kalimantan - Nanda Agustina; Fadma Yulianti; Mahyuddin Mahyuddin; Rizky Nastiti (LPPM Universitas KH A. Wahab Hasbullah, 2026)
This study aims to analyze the influence of soft skills, hard skills, and organizational experience on the work readiness of students at the Kalimantan Institute of Business and Technology. This research employs an associative quantitative (explanatory) approach with a questionnaire method. The research sample consists of 65 respondents selected using a census sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression analysis. The partial statistical test results indicate that soft skills and hard skills have a positive and significant effect on students' work readiness, while organizational experience has a positive but non-significant effect. Simultaneously, the three variables significantly influence students' work readiness. The coefficient of determination R2 of 0.748 indicates that 74.8% of the variation in work readiness can be explained by these three variables, while the remaining 25.2% is influenced by other factors outside the research model.